Analyzing multilevel data: comparing findings from hierarchical linear modeling and ordinary least squares regression - Rocconi, Louis M. (Higher education, 2013)
This study examined the differing conclusions one may come to depending upon the type of analysis chosen, hierarchical linear modeling or ordinary least squares (OLS) regression. To illustrate this point, this study examined the influences of seniors' self-reported critical thinking abilities three ways: (1) an OLS regression with the student as the unit of analysis, (2) an OLS regression with the institution as the unit of analysis, and (3) a three-level hierarchical linear model. Overall, results demonstrate that one would come to substantively different conclusions regarding the influences on students' perceived critical thinking ability depending upon the type of analysis chosen, especially in regards to the effects of the institutional characteristics.